Porcelainized polyurea coating and preparation method thereof
By using a combination of low-melting glass fiber and porcelain filler in polyurea coatings, the problems of poor construction performance and physical properties are solved, and the polyurea coating with high fire resistance is realized, forming a high-temperature and stable porcelain film. Significantly improves protection performance.
Patent Information
- Application Number
- CN202411643158.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-17
AI Technical Summary
The construction performance of existing polyurea coatings becomes worse after adding a large amount of porcelain filler, and their physical properties are seriously degraded, making it difficult to meet the needs of high fire resistance.
The ceramic-energizable polyurea coating is used to combine low-melting glass fiber and porcelain-forming filler to improve the structural strength and fire resistance of the coating through the combination of isocyanate prepolymer, mixed slurry and glass fiber.
It significantly improves the construction performance and fire resistance of the coating, forming a dense, hard, high-temperature and corrosion-resistant porcelain film, which significantly improves the protection performance.
Smart Images

Figure BDA0005139011730000051
Abstract
Description
Technical Field
[0001] The invention relates to a polyurea coating and a preparation method thereof, in particular to a ceramicizable polyurea coating and a preparation method thereof. Background Art
[0002] In recent years, polyurea coatings have developed rapidly, and their application fields have further expanded. The rapid expansion of market application fields has put forward higher performance requirements for polyurea coatings, especially in terms of fire protection. As we all know, polyurea coatings, as an organic coating, are a combustible material, but with the promotion of its application fields, people have put forward higher requirements on the fire resistance of polyurea coatings. Adding porcelain-forming fillers to polyurea coatings is an effective method to improve the fire resistance of coatings, but a large amount of porcelain-forming fillers will cause the construction performance of polyurea to deteriorate and the physical properties to deteriorate seriously. To this end, the present invention has developed a porcelain-able spray polyurea coating, which not only solves the problem that a large amount of porcelain-forming fillers fills the polyurea, resulting in poor construction performance and serious degradation of physical properties, but also has excellent fire resistance. Summary of the invention
[0003] Purpose of the invention: The purpose of the present invention is to provide a ceramic polyurea coating to solve the problem that the existing polyurea coating has poor construction performance and serious degradation of physical properties. Another purpose of the present invention is to propose a preparation method of a ceramic polyurea coating to solve the problem of how to prepare a ceramic polyurea coating.
[0004] Technical solution: The ceramic polyurea coating described in the present invention comprises an isocyanate prepolymer, a mixed slurry and glass fiber, wherein the mixed slurry comprises terminal amino polyether, terminal hydroxyl polysiloxane, a second chain extender, a catalyst, a ceramic filler and an adsorbent, and the melting point of the glass fiber is 350-600°C.
[0005] The present invention effectively improves the physical properties of the polyurea coating containing ceramic fillers by adding low-melting point glass fibers, thereby improving the construction performance of the coating and having excellent fireproof performance. The use of low-melting point glass fiber reinforced polyurea coating can not only significantly enhance the structural strength of the coating at room temperature, but also the low-melting point glass fiber can melt when the flame temperature is lower than 600°C, and cooperate with the ceramic fillers to enable the coating to quickly form a dense, hard, high-temperature stable, corrosion-resistant, and fireproof ceramic film at the early stage of a fire, thereby significantly improving the protective performance.
[0006] Preferably, the mass percentage of -NCO in the isocyanate prepolymer is 5-10%.
[0007] Preferably, the raw materials for preparing the isocyanate prepolymer include hydroxyl-terminated polysiloxane, a first chain extender and polyisocyanate.
[0008] Preferably, the terminal hydroxyl polysiloxane includes at least one of Dow PMX-0930, Wacker 4644A, and hydroxy silicone oil; the polyisocyanate includes at least one of diphenylmethane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, methylcyclohexyl diisocyanate, cyclohexane dimethylene diisocyanate, xylene dimethylene diisocyanate, and 1,4-cyclohexane diisocyanate; and the first chain extender includes at least one of ethylene glycol, 1,2-propylene glycol, 1,3-butanediol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, diethylene glycol, methylpropylene glycol, dipropylene glycol, and trimethylolpropane.
[0009] Preferably, the amount of each component in the mixed slurry is: 20-50 parts of amino-terminated polyether, 50-80 parts of hydroxyl-terminated polysiloxane, 5-10 parts of porcelain-forming filler, 5-20 parts of second chain extender, 0.1-1 parts of catalyst, and 3-10 parts of adsorbent, by weight.
[0010] Preferably, the amino-terminated polyether is at least one of D230, D2000, and T5000; the second chain extender includes diethyltoluenediamine, 3,5-dimethylthiotoluenediamine, 2,4-diamino-3,5-dimethylthiochlorobenzene, 4,4'-bis-sec-butylaminodiphenylmethane, N,N,-dialkylphenylenediamine, 2,4-diamino-3-methylthio-5-propyltoluene, 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane, 4,4,-bis-sec-butylaminodicyclohexylmethane, 3,3,-dimethyl-4,4, - at least one of bis-sec-butylamino-dicyclohexylmethane, trimethylhexanediamine or hydrogenated MDA; the catalyst includes at least one of organic tin, organic bismuth, triethylenediamine, bismorpholinyl diethyl ether, tetrabutyl titanate, and tetraisopropyl titanate; the porcelain-forming filler includes at least one of mica, wollastonite, diatomaceous earth, kaolin, and sepiolite; the adsorbent includes at least one of 3A activation powder, 4A activation powder, and 5A activation powder; the terminal hydroxyl polysiloxane includes at least one of Dow PMX-0930, Wacker 4644A, and hydroxyl silicone oil.
[0011] Preferably, the mass ratio of the isocyanate prepolymer, the mixed slurry and the glass fiber is 40-70:50-70:10-20.
[0012] Another aspect of the present invention discloses a method for preparing the above-mentioned ceramic polyurea coating, comprising the following steps:
[0013] (1) stirring and heating the terminal hydroxyl polysiloxane and the first chain extender, dehydrating the mixture under vacuum, releasing the vacuum, cooling the mixture to below 50° C., adding polyisocyanate, and heating the mixture again for reaction. After the reaction, the -NCO value of 5-10% is determined to be a qualified product. Cooling the mixture, discharging the mixture, and filtering the mixture to obtain an isocyanate prepolymer;
[0014] (2) placing the amino-terminated polyether, the hydroxy-terminated polysiloxane, the second chain extender, the catalyst, the porcelain-forming filler and the adsorbent into a high-speed mixer in sequence, stirring and mixing, and filtering the discharged material to obtain a mixed slurry;
[0015] (3) The isocyanate prepolymer, the mixed slurry and the glass fiber are uniformly mixed to obtain a vitrified polyurea coating.
[0016] Preferably, in step (1), the terminal hydroxyl polysiloxane and the first chain extender are stirred and heated to 95-100°C; the dehydration time is 5-7h; the reaction is heated to 90°C again for 3-5h; the discharge temperature does not exceed 70°C; the mass ratio of terminal hydroxyl polysiloxane: first chain extender: polyisocyanate is 20-50:2-5:5-25.
[0017] Preferably, in step (2), the stirring and mixing conditions are 10000-20000 r / min for 0.5-1.5 h, and then stopping the stirring and standing for 1-2 h; in step (3), the length of the glass fiber is 0.5-20 mm.
[0018] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0019] The coating formed by the ceramic polyurea coating prepared by the present invention has good physical properties, wherein the tensile strength can reach 20MPa, the elongation at break can reach 320%, the tear strength can reach 55MPa, and the DIN abrasion index can reach 34. At the same time, the polyurea material prepared by the present invention has good fire resistance. DETAILED DESCRIPTION
[0020] The technical solution of the present invention is further described below.
[0021] Example 1: A ceramic polyurea coating comprises an isocyanate prepolymer, a mixed slurry and glass fiber, wherein the mixed slurry comprises amino-terminated polyether, hydroxy-terminated polysiloxane, a second chain extender, a catalyst, a ceramic filler and an adsorbent, and the glass fiber has a melting point of 500°C.
[0022] The preparation method of the above-mentioned ceramic polyurea coating is as follows:
[0023] (1) By weight, 45 parts of Dow PMX-0930 and 5 parts of 1,4-butanediol were stirred and heated to 95° C., dehydrated under vacuum for 7 hours, released the vacuum, cooled to below 50° C., added 10 parts of isophorone diisocyanate, heated to 90° C. for reaction for 3 hours, and after the reaction, the -NCO value was measured to be 5-10% for qualified products, cooled to 70° C. for discharge, and filtered to obtain isocyanate prepolymer;
[0024] (2) By weight, 20 parts of D2000, 5 parts of T5000, 15 parts of Wacker 4644A, 8 parts of 4,4-bis-sec-butylaminodicyclohexylmethane, 1 part of diethyltoluenediamine (E100), 0.5 parts of organic bismuth catalyst, 0.2 parts of organic tin catalyst, 6 parts of mica powder, and 5 parts of 3A molecular sieve were successively put into a high-speed mixer, stirring was started, the speed was controlled to 15000 r / min and stirring was carried out for 1 hour, stirring was stopped and allowed to stand for 1.5 hours, and the mixed slurry was filtered out;
[0025] (3) The isocyanate prepolymer, the mixed slurry and the glass fiber with a length of 2 mm are evenly mixed in a mass ratio of 40:50:15 to obtain a vitrified polyurea coating.
[0026] Example 2: The preparation method of the ceramic polyurea coating is as follows:
[0027] (1) According to weight, 25 parts of Dow PMX-0930, 20 parts of Wacker 4644A, and 5 parts of 1,6-hexanediol were stirred and heated to 97° C., dehydrated under vacuum for 5 hours, released the vacuum, cooled to below 50° C., added with 10 parts of dicyclohexylmethane diisocyanate, heated to 90° C. for reaction for 5 hours, and after the reaction, the -NCO value was measured to be 5-10% for qualified products, cooled to 70° C. for discharge, and filtered to obtain isocyanate prepolymer;
[0028] (2) In parts by weight, 20 parts of D2000, 5 parts of T5000, 15 parts of Wacker 4644A, 8 parts of 3,3-dimethyl-4,4-bis-sec-butylamino-dicyclohexylmethane, 1 part of trimethylhexanediamine or hydrogenated MDA, 0.5 parts of organic bismuth catalyst, 0.2 parts of organic tin catalyst, 6 parts of mica powder, and 5 parts of 3A molecular sieve were successively put into a high-speed mixer, and stirring was started. The speed was controlled to 10000 r / min and stirring was carried out for 1.5 hours. After stopping stirring and standing for 1 hour, the material was filtered to obtain a mixed slurry.
[0029] (3) The isocyanate prepolymer, the mixed slurry and the glass fiber with a length of 0.5 mm are mixed uniformly in a mass ratio of 70:70:20 to obtain a vitrified polyurea coating. The melting point of the glass fiber is 600°C.
[0030] Example 3: The preparation method of the ceramic polyurea coating is as follows:
[0031] (1) According to weight, 25 parts of Dow PMX-0930, 20 parts of Wacker 4644A, and 5 parts of methyl propylene glycol were stirred and heated to 100° C., dehydrated under vacuum for 6 hours, released the vacuum, cooled to below 50° C., added with 10 parts of methyl cyclohexyl diisocyanate, heated to 90° C. and reacted for 4 hours. After the reaction was completed, the -NCO value was measured to be 5-10%, which was a qualified product, cooled to 70° C., discharged, and filtered to obtain an isocyanate prepolymer;
[0032] (2) In parts by weight, 20 parts of D2000, 5 parts of T5000, 15 parts of Wacker 4644A, 8 parts of 2,4-diamino-3,5-dimethylthiochlorobenzene, 1 part of 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane, 0.5 parts of an organic bismuth catalyst, 0.2 parts of an organic tin catalyst, 2 parts of kaolin, 4 parts of mica powder, and 5 parts of 4A molecular sieves were successively put into a high-speed mixer, stirring was started, the speed was controlled to be 20000 r / min, stirring was carried out for 1 hour, stirring was stopped, and the mixture was allowed to stand for 2 hours, and then the mixture was filtered to obtain a mixed slurry.
[0033] (3) The isocyanate prepolymer, the mixed slurry and the glass fiber with a length of 10 mm are mixed uniformly in a mass ratio of 60:65:15 to obtain a vitrified polyurea coating. The melting point of the glass fiber is 350°C.
[0034] Example 4: The preparation method of the ceramic polyurea coating is as follows:
[0035] (1) According to weight, 25 parts of Dow PMX-0930, 20 parts of Wacker 4644A, and 5 parts of 1,4-butanediol were stirred and heated to 95° C., dehydrated under vacuum for 5 hours, released the vacuum, cooled to below 50° C., added with 10 parts of phenylmethane diisocyanate, heated to 90° C. and reacted for 4 hours. After the reaction was completed, the -NCO value was measured to be 5-10%, which was a qualified product, cooled to 70° C., discharged, and filtered to obtain an isocyanate prepolymer;
[0036] (2) According to weight, 20 parts of D2000, 5 parts of T5000, 15 parts of Wacker 4644A, 8 parts of 4,4'-bis-sec-butylaminodiphenylmethane (Unilink4200), 1 part of diethyltoluenediamine (E100), 0.5 parts of organic bismuth catalyst, 0.2 parts of organic tin catalyst, 2 parts of kaolin, 2 parts of sepiolite powder, 2 parts of mica powder, and 5 parts of 3A molecular sieve were successively put into a high-speed mixer, and stirring was started. The speed was controlled to be 12000 r / min and stirring was carried out for 1 hour. After stopping stirring and standing for 1 hour, the material was filtered to obtain a mixed slurry.
[0037] (3) The isocyanate prepolymer, the mixed slurry and the glass fiber with a length of 1 mm are mixed uniformly in a mass ratio of 40:70:20 to obtain a vitrified polyurea coating. The melting point of the glass fiber is 400°C.
[0038] Example 5: The preparation method of the ceramic polyurea coating is as follows:
[0039] (1) By weight, 45 parts of Dow hydroxy silicone oil and 5 parts of trimethylolpropane were stirred and heated to 95° C., dehydrated under vacuum for 6 hours, released the vacuum, cooled to below 50° C., added with 10 parts of cyclohexane dimethylene isocyanate, heated to 90° C. and reacted for 4 hours. After the reaction was completed, the -NCO value was measured to be 5-10% for qualified products, cooled to 70° C., discharged, and filtered to obtain isocyanate prepolymer;
[0040] (2) According to weight, 20 parts of D2000, 5 parts of T5000, 15 parts of Wacker 4644A, 7 parts of diethyltoluenediamine, 2 parts of 3,5-dimethylthiotoluenediamine, 0.3 parts of triethylenediamine, 0.3 parts of bismorpholinyl diethyl ether, 5 parts of wollastonite, and 5 parts of 5A molecular sieve were successively put into a high-speed mixer, and stirring was started. The speed was controlled to be 12000 r / min and stirring was carried out for 1 hour. After stopping stirring and standing for 1 hour, the material was filtered to obtain a mixed slurry.
[0041] (3) The isocyanate prepolymer, the mixed slurry and the glass fiber with a length of 1 mm are mixed uniformly in a mass ratio of 40:70:20 to obtain a vitrified polyurea coating. The melting point of the glass fiber is 550°C.
[0042] Example 6: The preparation method of the ceramic polyurea coating is as follows:
[0043] (1) According to weight, 25 parts of Dow PMX-0930, 20 parts of hydroxy silicone oil, and 5 parts of neopentyl glycol were stirred and heated to 95°C, dehydrated under vacuum conditions for 5 hours, released the vacuum, cooled to below 50°C, added with 10 parts of 1,4-cyclohexane diisocyanate, heated to 90°C for reaction for 4 hours, and after the reaction, the -NCO value was measured to be 5-10% for qualified products, cooled to 70°C for discharge, and filtered to obtain isocyanate prepolymer;
[0044] (2) In parts by weight, 14 parts of D2000, 7 parts of T5000, 16 parts of Wacker 4644A, 9 parts of N,N-dialkylphenylenediamine, 2 parts of 2,4-diamino-3-methylthio-5-propyltoluene, 0.8 parts of tetrabutyl titanate, 2 parts of kaolin, 2 parts of sepiolite powder, 2 parts of mica powder, and 5 parts of 3A molecular sieve were successively put into a high-speed mixer, and stirring was started. The speed was controlled to be 12000 r / min and stirring was carried out for 1 hour. After stopping stirring and standing for 1 hour, the material was filtered to obtain a mixed slurry.
[0045] (3) The isocyanate prepolymer, the mixed slurry and the glass fiber with a length of 1 mm are mixed uniformly in a mass ratio of 40:70:20 to obtain a vitrified polyurea coating. The melting point of the glass fiber is 450°C.
[0046] Comparative Example 1: The rest is the same as Example 4, except that:
[0047] No glass fibers were added in step (3).
[0048] Comparative Example 2: The rest is the same as Example 4, except that:
[0049] Glass fiber with a melting point of 700°C is used.
[0050] Comparative Example 3: The rest is the same as Example 4, except that:
[0051] Glass fiber with a melting point of 800°C is used.
[0052] Comparative Example 4: The rest is the same as Example 4, except that:
[0053] Glass fiber with a melting point of 1000°C is used.
[0054] The coatings prepared in Examples 1-6 and Comparative Examples 1-4 were coated to obtain polyurea composite materials. First, a layer of release agent was brushed on smooth glass, and then a 3 mm thick polyurea composite material was sprayed using a special spraying device. After preliminary curing, the coating film was removed and cured in an oven (temperature 70° C.) for 72 hours. The physical properties and fire resistance of the polyurea composite material were tested in accordance with GB / T23446-2009, GB / T23441-2009, GB / T10707-2008, and DIN 50324 standards. The results are as follows:
[0055] Table 1 Effect of glass fiber on the performance of polyurea coating after molding
[0056]
[0057] The performance data of Comparative Example 1 in Table 1 are significantly lower than those of Example 4. It can be seen that when low-melting point glass fiber is not added, the ceramic filler will significantly reduce the physical properties and fire resistance of the polyurea coating after molding; while the physical and mechanical performance data of Comparative Examples 2-4 are basically close to those of Example 4, but the fire resistance limit is significantly reduced. It can be seen that although the addition of high-melting point glass fiber can also improve the physical properties of the coating, it will significantly reduce the fire resistance of the ceramic polyurea coating. In addition, it can be seen from Comparative Examples 2-4 that the fire resistance limit performance of the polyurea composite material is negatively correlated with the melting point of the glass fiber, indicating that the melting point of the glass fiber is crucial to the performance of the fire resistance of the glass fiber and is also a key factor affecting the performance of the polyurea coating after molding.
Claims
1. A ceramic polyurea coating, characterized in that: The invention comprises isocyanate prepolymer, mixed slurry and glass fiber, wherein the mixed slurry comprises amino-terminated polyether, hydroxy-terminated polysiloxane, a second chain extender, a catalyst, a porcelain-forming filler and an adsorbent, and the melting point of the glass fiber is 350-600°C.
2. The ceramicizable polyurea coating according to claim 1, characterized in that: The mass percentage of -NCO in the isocyanate prepolymer is 5-10%.
3. The ceramicizable polyurea coating according to claim 1, characterized in that: The raw materials for preparing the isocyanate prepolymer include terminal hydroxyl polysiloxane, a first chain extender and polyisocyanate.
4. The ceramicizable polyurea coating according to claim 3, characterized in that: The terminal hydroxyl polysiloxane includes at least one of Dow PMX-0930, Wacker 4644A, and hydroxy silicone oil; the polyisocyanate includes at least one of diphenylmethane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, methylcyclohexyl diisocyanate, cyclohexane dimethylene diisocyanate, xylene dimethylene diisocyanate, and 1,4-cyclohexane diisocyanate; the first chain extender includes at least one of ethylene glycol, 1,2-propylene glycol, 1,3-butanediol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, diethylene glycol, methylpropylene glycol, dipropylene glycol, and trimethylolpropane.
5. The ceramicizable polyurea coating according to claim 1, characterized in that: In parts by weight, the amount of each component in the mixed slurry is: 20-50 parts of terminal amino polyether, 50-80 parts of terminal hydroxyl polysiloxane, 5-10 parts of porcelain-forming filler, 5-20 parts of the second chain extender, 0.1-1 parts of the catalyst, and 3-10 parts of the adsorbent.
6. The ceramicizable polyurea coating according to claim 5, characterized in that: The amino-terminated polyether is at least one of D230, D2000, and T5000; the second chain extender includes diethyltoluenediamine, 3,5-dimethylthiotoluenediamine, 2,4-diamino-3,5-dimethylthiochlorobenzene, 4,4'-bis-sec-butylaminodiphenylmethane, N,N,-dialkylphenylenediamine, 2,4-diamino-3-methylthio-5-propyltoluene, 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane, 4,4,-bis-sec-butylaminodicyclohexylmethane, 3,3,-dimethyl-4,4,-di At least one of sec-butylamino-dicyclohexylmethane, trimethylhexanediamine or hydrogenated MDA; the catalyst includes at least one of organic tin, organic bismuth, triethylenediamine, bismorpholinyl diethyl ether, tetrabutyl titanate, tetraisopropyl titanate; the porcelain-forming filler includes at least one of mica, wollastonite, diatomaceous earth, kaolin, and sepiolite; the adsorbent includes at least one of 3A activation powder, 4A activation powder, and 5A activation powder; the terminal hydroxyl polysiloxane includes at least one of Dow PMX-0930, Wacker 4644A, and hydroxyl silicone oil.
7. The ceramicizable polyurea coating according to claim 1, characterized in that: The mass ratio of the isocyanate prepolymer, the mixed slurry and the glass fiber is 40-70:50-70:10-20.
8. A method for preparing the ceramicizable polyurea coating according to any one of claims 1 to 7, characterized in that: The steps include: (1) stirring and heating the terminal hydroxyl polysiloxane and the first chain extender, dehydrating the mixture under vacuum, releasing the vacuum, cooling the mixture to below 50° C., adding polyisocyanate, and heating the mixture again for reaction. After the reaction, the -NCO value of 5-10% is determined to be a qualified product. Cooling the mixture, discharging the mixture, and filtering the mixture to obtain an isocyanate prepolymer; (2) placing the amino-terminated polyether, the hydroxy-terminated polysiloxane, the second chain extender, the catalyst, the porcelain-forming filler and the adsorbent into a high-speed mixer in sequence, stirring and mixing, and filtering the discharged material to obtain a mixed slurry; (3) The isocyanate prepolymer, the mixed slurry and the glass fiber are uniformly mixed to obtain a vitrified polyurea coating.
9. The method for preparing the ceramicizable polyurea coating according to claim 8, characterized in that: In step (1), the terminal hydroxyl polysiloxane and the first chain extender are stirred and heated to 95-100°C; the dehydration time is 5-7h; the reaction is heated to 90°C again for 3-5h; the discharge temperature does not exceed 70°C; the mass ratio of terminal hydroxyl polysiloxane: first chain extender: polyisocyanate is 20-50: 2-5: 5-25.
10. The method for preparing the ceramicizable polyurea coating according to claim 8, characterized in that: In step (2), the stirring and mixing conditions are 10000-20000 r / min for 0.5-1.5 h, then stopping the stirring and standing for 1-2 h; in step (3), the length of the glass fiber is 0.5-20 mm.
Citation Information
Patent Citations
Self-repairing ceramic silicone rubber material and preparation method thereof
CN110183858A
High-temperature vulcanized silicone rubber with both electrical conductivity and ceramization potential, and preparation method thereof
CN112111159A
Anticorrosive polyurea coating for petrochemical industry and preparation method thereof
CN112280448A
High-strength sound-insulation polyurethane urea composite material
CN112679941A